2010
DOI: 10.1111/j.1447-0756.2010.01207.x
|View full text |Cite
|
Sign up to set email alerts
|

Are heterochromatin polymorphisms associated with recurrent miscarriage?

Abstract: The overall high incidence of chromosome polymorphisms in patients with recurrent miscarriages compared to the normal population needs to be confirmed with additional investigations including larger populations in order to delineate the role of 'harmless' chromosomal aberrations in the etiology of recurrent spontaneous abortions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
24
1
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 8 publications
2
24
1
1
Order By: Relevance
“…In recent years, more and more studies have shown an increased incidence of chromosomal polymorphism variation in infertile couples [20,21]. Some studies have demonstrated that 2.0–14.0% of infertile men have constitutional chromosomal abnormalities [20,21].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, more and more studies have shown an increased incidence of chromosomal polymorphism variation in infertile couples [20,21]. Some studies have demonstrated that 2.0–14.0% of infertile men have constitutional chromosomal abnormalities [20,21].…”
Section: Discussionmentioning
confidence: 99%
“…Most often, chromosomes vary in size and position of heterochromatin in the 1qh, 9qh, and 16qh regions. Although inherited variants have been reported not to be associated with any risk for phenotypic abnormalities, chromosomal heteromorphisms have been found to have a higher frequency relative to the normal population and have been regarded as abnormalities in some studies [11,17,20,21]. Recent studies suggest that classical euchromatic variants of 9qh+/12qh+ and heteromorphism on chromosome 6q may be responsible for recurrent abortions [29,30].…”
Section: Discussionmentioning
confidence: 99%
“…Cytogenetic research conducted on patient groups with recurrent pregnancy loss reports between 4 and 18.9% chromosome heteromorphism, which is higher than the normal population, and it has been suggested that these cases of heteromorphism may be associated with fetal loss (Makino et al, 1990;Düzcan et al, 2003;Sahin et al, 2008;De la FuenteCortés et al, 2009;Caglayan et al, 2010). However, comparative studies with control groups have yielded contradictory results.…”
Section: Discussionmentioning
confidence: 98%
“…In this respect, there are many studies suggesting that there is no relationship between control groups and couples with fetal loss (Blumberg et al, 1982;de Braekleer and Dao, 1990). In recent studies, however, Caglayan et al (2010) have reported a statistically higher rate of chromosome heteromorphism in the patient group (8%) compared to the control group (4%), suggesting that if the patients experiencing recurrent abortion have such heteromorphisms, their chances for further abortions may be higher than other populations without such heteromorphisms in future pregnancies. Sahin et al (2008) found a statistically higher rate of chromosome heteromorphism in infertile couples (6.52%) compared to the control group (1.77%).…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, research has demonstrated that Y chromosome polymorphisms could contribute to homologous chromosome pairing and chromosome segregation. However, Y chromosome polymorphisms could also discourage homologous chromosome pairing during the cell division phase, thus causing disorders such as cell division disorder, embryonic developmental disorder, teratogenic disorders, stillbirth and miscarriage [23,24]. The clinical symptoms of URM are further analysed and compared with the characteristics of individuals carrying normal Y chromosomes.…”
Section: Discussionmentioning
confidence: 99%